Cross-acceleration and the relationship between board independence and bond yield spreads. (March 2019) - Meder, Anthony A.; Schwartz, Steven T.; Young, Richard
Abstract: This paper investigates the mediating effect of cross-acceleration provisions in bond debt on board independence and bond yield spreads. Cross-acceleration provisions cause bond debt to accelerate if other debt (mainly bank debt) is accelerated and allows bondholders to benefit from the monitoring of fellow creditors. Board independence, while generally seen as a positive governance feature, has been viewed as detrimental to bondholder interests when bondholder-shareholder conflicts are high. Cross-acceleration works to protect bondholder interests through increased likelihood of bankruptcy court supervision (or early repayment of debt). Consistent with this view, we find that when bondholder-shareholder conflict are high bonds issued without cross-acceleration provisions have yields that increase in board independence whereas bonds issued with cross-acceleration have yields that decrease in board independence. The results suggest that cross-acceleration plays a role in mitigating the tendency of more independent boards to favor shareholders when bondholder-shareholder conflicts arise.